Penerapan Metode STEM pada Proses Pembelajaran Fisika Berbais Pendekatan Saintifik untuk Meningkatkan Keterampilan Berpikir Kritis - Himsar, Himsar; Harahap, Fitra Hayati (Gravity Journal, 2024)
The learning process using one method of learning creates a learning atmosphere of saturation, boredom and tiredness. students become weak and lazy in participating in learning. Students do not understand and are confused when faced with integrated concepts (integrated science, technology, engineering and mathematics material). The integrity and integration of these materials requires a long time to analyze and conclude. This condition of students has an impact on their critical thinking skills being weak, their way of finding solutions to problems is not being able to solve problems. The integrity and integration of science, technology, engineering and mathematics materials requires a high level of critical thinking among students. Researchers provide solutions to these problems by applying STEM methods to physics learning based on a scientific approach. This research can improve students' abilities in the areas of knowledge, attitudes, skills and critical thinking. This research uses PTK with two cycles. The average value for Cycle I is knowledge 65, attitude 67, skills 68 with a KKM of 70. Cycle I has not yet been completed and continues with cycle II, the average value for Cycle II is knowledge 75, attitude 77 and skills 80, meaning that all areas of student ability are above KKM 70, meaning complete. For critical thinking skills, researchers refer to the average score of students on the initial test of 63.66 (value of knowledge, attitudes and skills). In cycle I, the average critical thinking score for students was 68, an increase of 4.34 on the scale or 6.54%. The average critical thinking score of cycle I has not increased sufficiently, so it continues with cycle II. The average critical thinking score for Cycle II students was 75. Cycle II experienced an increase of 11.34 on the scale or 17.8% from the average initial test score of 63.66. with this improvement, the application of STEM methods to the physics learning process based on a scientific approach can improve students' critical thinking abilities.